Division the Husband and Wife Roles to Live a Domestic Life During the Pandemic Covid 19 in the Mubadala Perspective - Nur Lailatul Musyafaah; Yeni Novitasari; Tri Leli Rahmawati (Sultang Agung Islamic University, 2021)
This article discusses the division of roles between husband and wife during a pandemic in the Mubadalah perspective. Due to the coronavirus, there are changes in social life, including family life, which impacts the division of roles between husband and wife in domestic life. The Mubadalah is a concept that discusses gender equality by emphasizing the principle of mutual benefit from two people who are related. Women and men have the same rights and opportunities to take part in the public and domestic sphere and take advantage of all life aspects. This research aimed to determine and analyze the division of roles between husband and wife during the pandemic from the Mubadalah perspective. This research was qualitative field research. The data was collected through interviews and documentation, then analyzed with deductive reasoning. This research concluded the roles of husband and wife in the family during this pandemic were according to the agreement between husband and wife in the economy, educate children, fand house chores. That was based on the conditions and situations faced by the couple. The husbands’ role was still dominant in economic fulfillment. However, it did not prevent the wives from helping and supporting the family economy. Conversely, educating children and house chores was still dominated by the wives, although it did not prevent the husbands from taking part in informing the children and house chores. It shows that the concept of Mubadalah has not been applied to the division of roles between husband and wife in the family during the pandemic because both husband and wife should have equal rights and opportunities in carrying out activities in the domestic and public sphere.